2021
DOI: 10.2147/nss.s332474
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture: A Promising Approach for Comorbid Depression and Insomnia in Perimenopause

Abstract: Comorbid depression and insomnia are ubiquitous mental complaints among women going through the perimenopausal stage of life and can result in major decline in quality of life. Antidepressive agents combined with/without hypnotics, and/or hormone therapy are currently the most common treatment for perimenopausal depression (PMD) and insomnia (PMI). Balancing the benefits of these pharmacotherapies against the risk of adverse events (AEs) is a difficult task for both clinicians and women. There has been a growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 113 publications
0
21
0
Order By: Relevance
“… 10 , 40 Although the mechanisms underlying acupuncture for treating depression-related insomnia are not fully elucidated, as a key component of traditional Chinese medicine, acupuncture is likely to work through multi-level and multi-target pathways, and the therapeutic effect of acupuncture on depression-related insomnia is possibly mediated through a variety of actions and mechanisms, such as modulating neurotransmitter, oxidative stress, signaling pathways, hypothalamic-pituitary-adrenal axis, and other cellular events. 40 For instance, experimental studies reveal that the antidepressant-like effect of acupuncture can be mediated by inhibition of inflammatory mediators via modulation of NF-κB in the prefrontal cortex and hippocampus. 41 The present study has several advantages to be addressed as follows.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 40 Although the mechanisms underlying acupuncture for treating depression-related insomnia are not fully elucidated, as a key component of traditional Chinese medicine, acupuncture is likely to work through multi-level and multi-target pathways, and the therapeutic effect of acupuncture on depression-related insomnia is possibly mediated through a variety of actions and mechanisms, such as modulating neurotransmitter, oxidative stress, signaling pathways, hypothalamic-pituitary-adrenal axis, and other cellular events. 40 For instance, experimental studies reveal that the antidepressant-like effect of acupuncture can be mediated by inhibition of inflammatory mediators via modulation of NF-κB in the prefrontal cortex and hippocampus. 41 The present study has several advantages to be addressed as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been regarded as a potentially effective drug-free approach for helping to treat mental illness and sleep disorders. 17 , 18 , 19 A previous study 20 demonstrated that acupuncture effectively improves sleep efficacy and prolongs total sleep time in patients with primary insomnia. A pilot study on electroacupuncture (EA) for the treatment of depression-related insomnia 21 found that patients experienced significant improvement in sleep quality after receiving EA treatment during a 12-week study period.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Acupuncture treatment upholds a holistic concept, so it can regulate and treat PDD at multiple levels, links, and targets, such as regulation of sex hormones, neurotransmitters, hypothalamic-pituitary-adrenal axis, hypothalamic-pituitary-ovarian axis, oxidative stress, signaling pathways, and other cellular events. [ 14 ] Acupuncture can compensate for the inability of SSRIs to address multisystem disorders in PDD. Unluckily, acupuncture is difficult to achieve short-term results for severe depressive disorder.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of acupuncture and SSRIs in the treatment of depressive disorder has been proven to have increased efficacy and reduced side effects, which may provide a new direction for clinical treatment [13] . Acupuncture treatment upholds a holistic concept, so it can regulate and treat PDD at multiple levels, links, and targets, such as regulation of sex hormones, neurotransmitters, hypothalamic-pituitary-adrenal axis, hypothalamic-pituitary-ovarian axis, oxidative stress, signaling pathways, and other cellular events [14] . Acupuncture can compensate for the inability of SSRIs to address multisystem disorders in PDD.…”
Section: Introductionmentioning
confidence: 99%